Associations and law : the classical and early Christian stages - Gierke, Otto von, 1841-1921 (Heritage., 1977)
George Heiman has translated the discussion of classical and early Christian laws of association from the major works by Grotto Gierke, Das deutsche Genossenschaftsrecht, bringing into English the eminent German jurist's historical analysis of the law.